Analysis of the Application of SAK EMKM on MSMEs at Wildan Shops in Talang Kuning Village, Teras Terunjam District, Mukomuko Regency, Bengkulu Province - Yuni Prawita; Neri Susanti; Zahrah Indah Ferina (Journal of Indonesian Management, 2021)
The purpose of this study is to determine the condition of the financial statements and the application of SAK EMKM at Wildan Shop UMKM. SAK EMKM is an accounting standard prepared by DSAK for micro, small and medium enterprises. This study uses a descriptive approach. To find out the application of SAK EMKM at the shop, the researcher used direct observation and interview techniques. The results showed that the shop did not record financial statements in accordance with SAK EMKM and there was no structured and detailed recording of income and expenses in its accounting reports. In making the financial statements, the shop makes records based on their own wishes without applying SAK EMKM and focuses on meeting needs and income in the business without considering accounting matters in accordance with SAK EMKM. Thus, the shop as a whole has made a mistake even though basically it can still run and continue to grow.